People, not just places: Expanding physical and social vulnerability indices by psychological indicators. Issue 4 (25th August 2021) - Babcicky, Philipp; Seebauer, Sebastian
Abstract: Damage and disruption caused by floods do not just arise from the characteristics of physical structures, but also from the characteristics of residents inhabiting these structures. Social vulnerability analyses typically employ socio‐demographic proxy indicators that do not address the risk attitudes, beliefs and agency of those living in areas at risk. To close this gap, this article introduces a range of indicators from psychological risk research. Physical, social and psychological indicators are compared for their influence on vulnerability outcomes such as building damage or emotional distress. Based on survey data of 456 Austrian at‐risk households, hierarchical regression models confirm the added value of psychological indicators for measuring vulnerability above and beyond traditional physical and social indicators. Our findings show that psychological indicators are particularly important for explaining health impacts and distress. General intentions for flood preparedness, fear of flooding and self‐efficacy are most relevant. For a more holistic view of vulnerability, measurement instruments should incorporate psychological indicators. Disaggregated household‐level data is necessary to fully capture the variability between households living in the same flood‐prone area. Indicators perform differently depending on the other indicators included, and the considered outcome; therefore, we caution against pooling indicators to composite indices of overall vulnerability.